2017
DOI: 10.7601/mez.68.19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabolic detoxifying enzymes in an insecticide resistant strain of <i>Aedes aegypti</i> harboring homozygous S989P and V1016G <i>kdr</i> mutations

Abstract: Important insecticide resistance mechanisms in the dengue vector Aedes aegypti are mutations of voltage-gated sodium channel (VGSC) genes or knockdown resistance (kdr) and increased activity of metabolic enzymes. The objective of this study was to determine activity of mixed-function oxidases (MFO), esterases and glutathione-s-transferases (GSTs) in two strains of Ae. aegypti. The UPK-R strain, which harbors S989P and V1016G homozygous mutations in the VGSC, was compared with the wild-type PMD strain. Adult bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…aegypti larvae prior to treatment with P. crispum oil demonstrated significantly higher levels of some detoxifying enzymes, such as GSTs, α-/β-ESTs, ACP and MFO in resistant PMD-R and/or UPK-R, than those in susceptible MCM-S. These findings were in agreement with those of many biochemical studies, which evaluated various pest species in either laboratory or field populations, and demonstrated increased levels of detoxifying enzymes such as GSTs [48,49], α-/β-ESTs [29,[50][51][52][53], ACP [54,55], and MFO [56][57][58] [15,59], and elevation of enzyme activity implicate an enhancer in the tolerance of mosquitoes to insecticides [50,51,60,61]. In consequence, resistance to some insecticides has been linked to an increment in insecticide metabolism through the up-regulation or structural changes of detoxifying enzymes [62,63].…”
Section: Resultssupporting
confidence: 84%
“…aegypti larvae prior to treatment with P. crispum oil demonstrated significantly higher levels of some detoxifying enzymes, such as GSTs, α-/β-ESTs, ACP and MFO in resistant PMD-R and/or UPK-R, than those in susceptible MCM-S. These findings were in agreement with those of many biochemical studies, which evaluated various pest species in either laboratory or field populations, and demonstrated increased levels of detoxifying enzymes such as GSTs [48,49], α-/β-ESTs [29,[50][51][52][53], ACP [54,55], and MFO [56][57][58] [15,59], and elevation of enzyme activity implicate an enhancer in the tolerance of mosquitoes to insecticides [50,51,60,61]. In consequence, resistance to some insecticides has been linked to an increment in insecticide metabolism through the up-regulation or structural changes of detoxifying enzymes [62,63].…”
Section: Resultssupporting
confidence: 84%
“…Although temephos resistance has been linked to increased levels of esterases, the specific esterase and inhibitors have not been identified [49]. Increased MFO activity has been suggested to play a partial role in pyrethroid resistance as well with kdr acting as the major mechanism [50].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti [ 114 ]. The latest study demonstrated that the aforementioned enzymes were either unrelated or merely contributed partially in pyrethroid resistance [ 115 ]. In regards to the discrepancies of these enzymes as contributory factors to pyrethroid resistance in Ae.…”
Section: Present Situation Of Pyrethroid Susceptibility In mentioning
confidence: 99%